Um estudo semântico-pragmático sobre os processos implícitos encontrados em construções binárias por inferência na hipotaxe adverbial - COSTA, Wanessa do Espírito Santo Queiroz (2025)
This article carries out a discussion of syntactic-semantic nature about binary constructions found in interactional acts that show implicit processes through interference in adverbial hypotaxis, videlicet: “Mais um Pio, eu retiro de sala”, This construction analyzed functional bias can be seen that it infers semantic values of time, cause and condition. Furthermore, it is important to highlight that this research is the result of debates that occurred in the Núcleo Amazônico de Estudos Semânticos de Português - NAESP, which was part of as a fellowship researcher and these debates were primordial to the reseach's development which also aims to explain the process that leads to the creation of binary constructions by inference in adverbial hypotaxis. Therefore, this work is based on the assumptions of the Functional Language, in the line of Bybee (2010) and on the work of Decat (2001), that advocate about the language's relation with other cognitive abilities, hence, construction that escape the syntactic standards are not created randomly, but motivated. Thus, to perform said discussion resorted to social media, with the purpose of collecting data that externalizes the omission of terms in a sentence complex.